Factor structure of the CES-D-20 scale in young adults in Singapore: An examination of six alternative structures and measurement invariance by sex - MAJEED, Nadyanna M. (Institutional Knowledge at Singapore Management University, 2024)
Building on past research that has indicated cultural variations in the factor structure of the 20-item Center for Epidemiologic Studies Depression Scale (CES-D-20), as well as several limitations validating the CES-D-20 within a Singapore context, this study investigated the CES-D-20's factor structure and sex-based measurement invariance in Singapore. A large young adult sample in Singapore (N = 1008) was utilised, and the original CES-D-20 was administered to all participants. The findings confirmed the four-factor model's robustness over five other alternative models (RMSEA = .05, SRMR = .04), where each of the 20 items loaded significantly onto its respective factor (all loadings≥.42, all ps ps